THE EFFECT OF IMPLEMENTING FINANCIAL ACCOUNTING STANDARDS (SAK) ON THE QUALITY OF FINANCIAL REPORTS IN PUBLIC COMPANIES IN INDONESIA - Lamtiur Lidia Gultom; Ayu Teresia Hutauruk; Mei Veronika Sri Endang Siagian (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to systematically examine the effect of the implementation of Financial Accounting Standards (FAS) on the quality of financial reports in public companies in Indonesia. Through a literature review approach, this study collects and analyzes findings from various scientific journals, textbooks, and official reports from related institutions such as IAI, OJK, and BEI. The results of the study indicate that the implementation of FAS, especially those that have adopted the principles of International Financial Reporting Standards (IFRS), generally has a positive impact on increasing the relevance, reliability, and comparability of financial reports. However, the effectiveness of implementation is highly dependent on contextual factors such as human resource readiness, accounting information system support, and supervision from capital market authorities. This study also identifies differences in the effect of FAS between industrial sectors and company sizes, and finds that there are still research gaps, especially the lack of longitudinal studies and the lack of contextual approaches in Indonesia. The theoretical implications of these findings are the importance of considering institutional and social factors in accounting studies, while the practical implications include the need to strengthen the company's internal capacity and regulatory supervision to ensure the quality of financial reporting in accordance with standards. This research contributes to enriching the literature on financial accounting in emerging markets and serves as a basis for further, more in-depth and contextual studies.